THE IMPORTANCE AND NECESSITY OF LABOR STANDARDS IN THE CONTEXT OF ECONOMIC MODERNIZATION - Umurzakova Zamira Salijanovna (Galaxy International Interdisciplinary Research Journal, 2024)
Work is a fundamental and universal category, encompassing multifaceted concepts that warrant comprehensive study as objects of research and improvement. In this context, labor measurement plays a crucial role. It involves determining the time required for a skilled workforce to perform specific tasks or services at varying levels of labor intensity, using diverse methods and tools.